The Introduction of Geobox Media to Develop Mathematical Logical Intelligence on Early Childhood - Nadiya Ulya; Erni Munastiwi (Jurusan PIAUD IAIN Syekh Nurjati Cirebon, 2021)
At this time the child's ability in logical mathematics still needs to be developed in various ways, one of which is by playing. In the process of playing, it cannot be separated from the media, to develop mathematical logic intelligence, media related to numbers and geometric shape patterns are needed, such as playing Geobox media. This article aims to determine the increase in children's mathematical logic intelligence using GeoBox playing media. The type of research used is PTK (Classroom Action Research) in which the research subjects are 10 children who are in TPA Qurratu'Ain in Harusan, South Kalimantan, the results of this study indicate that the GeoBox playing media is able to make children's mathematical logic intelligence increase pre-cycle, which was initially 10, 0 then becomes 12.5 in cycle I and cycle II as much as 15.5%. The intelligence possessed by children can be developed in an appropriate and appropriate way for the child, therefore the selection of tools for children's play must be carefully selected so that this development can be optimal.